Arthroscopic Management of Intraosseous Tophaceous Gout of the Knee: A Case Report and Review of the Literature - Yi-Jung Ma; Yu-Pao Hsu; Chao-Yang Wang (Formosan Journal of Musculoskeletal Disorders)
Intraosseous gouty tophi in the epiphysis of the femur is extremely rare. As the tophus signal intensity in magnetic resonance (MR) imaging is not pathognomonic of gout, arthroscopy for intra-articular intraosseous tophaceous gout of the knee could provide an effective tool for diagnosis and management. To the best of our knowledge, we present the first case of intraosseous gouty tophi of the knee treated arthroscopically by combining allograft, curettage, and debridement. At the 18-month follow-up point, radiographs revealed that the allograft and native bone were well-coalesced and there was no evidence of joint line collapse. The patient achieved a favorable outcome.